Uporaba eksperimentalne ekonomije za oceno omejene finančne racionalnosti - Ule, Aljaž (Teorija in praksa, 2018)
Using a laboratory experiment with human subjects and real stakes we investigate the limits of the classic economic idea of individual rationality. Three groups of between 14 and 16 student volunteers were given a choice between a lottery with a 50% chance to win 5 euros, and an equivalent, but distinctly framed lottery with an additional bonus. While economic theory postulates that rational individuals should always pick the lottery with a bonus, we observe that almost 50% of the subjects do not. The observed choices are not influenced by gender or the study discipline of the subjects. The experiments were prepared according to the rules of experimental economics, where all key decisions must be salient. That is, there were no hypothetical choices and all decisions had real monetary consequences for the subjects. In this way, our experimental economic method increased the external validity of the observed results.
Keywords: Decision making; Eksperimentalna ekonomija; Experimental economics; Odločanje; Racionalnost; Rationality